Tinea manuum: a 5 year retrospective study of demographic data, clinical characteristics, and treatment outcomes - Panittra Suphatsathienkul; Pattriya Jirawattanadon; Lalita Matthapan; Waranyoo Prasong; Chatisa Panyawong; Akkarapong Plengpanich; Sumanas Bunyaratavej; Charussri Leeyaphan (Scientific Reports)
Abstract Tinea manuum is a superficial fungal infection affecting the hands, particularly the palms and interdigital areas. This retrospective study investigated clinical features, laboratory findings, treatment, and outcomes in patients with fungal hand infections at Siriraj Hospital between 2016 and 2020. Among 107 patients, representing 1.3% of those with fungal skin infections, 64.5% were male, with a mean age of 54.3 ± 18.5 years. Diabetes mellitus was present in 26.2%, and 23.4% had prior topical steroid use. The most common symptom was itching (75.7%), while palm-scale (85.9%) was the most prevalent clinical finding. Concurrent fingernail onychomycosis was observed in 43%, and 59.8% had additional fungal skin infections. Among 50 positive cultures, dermatophytes accounted for 86% and nondermatophytes for 14%, with Trichophyton rubrum (54%) and Trichophyton mentagrophytes complex (24%) being the most frequent pathogens. Systemic antifungal treatment was administered to 57% of patients, with a mycological cure rate of 56.4%. A complete cure was achieved in 60.5% of dermatophyte infections but in none of the nondermatophyte cases (p = 0.003). These findings highlighted that tinea manuum could be caused by both dermatophytes and nondermatophytes, with significantly poorer outcomes observed in nondermatophyte infections. Concurrent fungal skin and nail infections should be evaluated for optimal management.